Intra‐tracheal surfactant/budesonide versus surfactant alone: Comparison of two consecutive cohorts of extremely preterm infants. Issue 7 (4th May 2021) - Moschino, Laura; Nardo, Daniel; Bonadies, Luca; Stocchero, Matteo; Res, Giulia; Priante, Elena; Salvadori, Sabrina; Baraldi, Eugenio
Abstract: Objectives: To compare the efficacy of intra‐tracheal (IT) surfactant/budesonide (SB) with that of surfactant alone (S) in reducing the rate of bronchopulmonary dysplasia (BPD) at 36 weeks post‐menstrual age (PMA), we included extremely preterm very low birth weight (VLBW) infants with severe respiratory distress syndrome (RDS) in our tertiary neonatal level of care unit (Padua, Italy). Study Design: A retrospective chart review of two cohorts of extremely preterm VLBW neonates (<28 +0 gestation weeks, birth weight [BW] < 1500 g) born in two consequent epochs (2017–2018/2018–2019) were compared. The SB group received surfactant (200 mg/kg 1st dose) and budesonide (0.25 mg/kg), while the S group received surfactant alone. Results: Among 68 neonates with RDS Grades III–IV, FiO2 ≥ 0.3 within 12 h of life, 18 were included in each group after matching for perinatal, clinical, and laboratory characteristics. IT SB did not affect the rate of BPD (Vermont Oxford Network, Jensen's, and National Institute of Child Health and Human Development BPD Workshop 2018 definitions), death, BPD, or death at 36 weeks PMA. Hypotension requiring inotropic support within the first 5 days was lower in those receiving the combined treatment ( p = .03). The SB group had fewer admissions to pediatric ward due to respiratory causes up to 12 months of corrected age ( p = .03). Conclusion: The preliminary results of this retrospective study suggest that in extremely preterm VLBW infants, IT SB for severe RDS did not affect the incidence of BPD, death, and BPD or death at 36 weeks PMA, compared to surfactant alone. The combined therapy proved to be safe in this population. Further studies are warranted to explore the role of early IT steroids on respiratory morbidity in preterm infants.